A molecular analysis of the Gelechiidae (Lepidoptera, Gelechioidea) with an interpretative grouping of its taxa. (11th March 2013) - KARSHOLT, OLE; MUTANEN, MARKO; LEE, SANGMI; KAILA, LAURI
<x xml:space="preserve">Abstract</x> We re‐examine the higher level phylogeny and evolutionary affinities of the family Gelechiidae (Lepidoptera: Gelechioidea) based on DNA sequence data for one mitochondrial gene (cytochrome c oxidase subunit I) and seven nuclear genes (Elongation Factor‐1α, wingless, Ribosomal protein S5, Isocitrate dehydrogenase, Cytosolic malate dehydrogenase, Glyceraldehyde‐3‐phosphate dehydrogenase and Carbamoylphosphate synthase domain protein). Fifty‐two taxa representing nearly all established subfamilies and tribes of Gelechiidae, and about 10% of described gelechiid genera, in addition to five outgroup taxa were sequenced. Data matrices (6157 bp total) were analysed under model‐based evolutionary methods (Maximum Likelihood and Bayesian Inference), resulting in novel high‐level phylogenetic interrelationships. The best supported cladogram divided the Gelechiidae into six distinct clades corresponding to the subfamilies Anacampsinae, Dichomeridinae, Apatetrinae, Thiotrichinae, Anomologinae and Gelechiinae (+ Physoptilinae, which were not available for study). The results suggest the following adjustments in gelechiid interrelationships: Brachmini is nested within Dichomeridinae; Anarsiini is the sister group of Chelariini; Pexicopiinae is the sister group of Apatetrinae, here suggested to be treated as a tribe Pexicopiini of Apatetrinae. A new subfamily Thiotrichinae (subfam.n.) is proposed on the basis of the resurrected genus Thiotricha Meyrick (gen.rev.), which includes Macrenches Meyrick, Palumbina Rondani and Polyhymno Chambers. Gelechiidae display a wide array of life‐history strategies, but the diversity in patterns of larval mode of life has direct phylogenetic correlation only below subfamily level, suggesting multiple origins and/or frequent reversals for traits such as external or internal feeding and leaf mining within the family.